Answer:
![g(x)\text{= (}(1)/(4))^(x+2)](https://img.qammunity.org/2023/formulas/mathematics/high-school/afzd69knjpey59ipxsliqxzin6ewbw0oj9.png)
Explanations:
An exponential function is given by the equation:
![y=ab^x](https://img.qammunity.org/2023/formulas/mathematics/high-school/hye5rg1h8wj3ohgdt4j1vpepdhoym0w9ex.png)
For the points (-2, 1) and (1, 1/64)
![x_1=-2,y_1=1,x_2=1,y_2=(1)/(64)](https://img.qammunity.org/2023/formulas/mathematics/high-school/ntfo50q8itjamzgs8rimf0aglxalaafbkw.png)
Substitute x₁, y₁, x₂, and y₂ into the functions to form two equations
![\begin{gathered} y_1=ab^(x_1) \\ y_2=ab^(x_2) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/1c42zdfo7ujj4ah1z7wqmthyystic77xhd.png)
![\begin{gathered} \text{1 = }ab^(-2)\ldots\ldots(1) \\ (1)/(64)=ab^1\ldots\ldots.(2) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/53v74x0pzi366800lzungz3kewt67u5hch.png)
Divide equation (2) by equation (1)
![\begin{gathered} (1)/(64)=\text{ }(ab^1)/(ab^(-2)) \\ (1)/(64)=b^3 \\ b\text{ = }\frac{1}{\sqrt[3]{64}} \\ \text{b = }(1)/(4) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/dcf657rt7aawc4w3iioxcf2y2sn07uzp2r.png)
Substitute the value b = 1/4 into the equation (2)
![\begin{gathered} (1)/(64)=a\text{ }(1)/(4) \\ \text{a = }(4)/(64) \\ \text{a = }(1)/(16) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/eydhf7cdk98bibt7epvvd50cabu4mk7kz5.png)
![\begin{gathered} \text{Substituting the values of a and b into g(x) = ab}^x \\ g(x)\text{ = }(1)/(16)((1)/(4))^x \\ \text{g(x)= (}(1)/(4))^2((1)/(4))^x \\ g(x)\text{ = (}(1)/(4))^(x+2) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/4tb4qr5vq3ggjmud8avkwr0r7d65o35hsb.png)